Novel teaching tool for the conversion of financial interest rates (GEON Journal (Management, Organizations and Business), 2020)
The conversion of rates or equivalence of interest rates is the initial and fundamental basis for the proper understanding of the topics of financial mathematics.Traditional methods are all effective (they achieve their objective), but at the same time they are very complex and often not as efficient in the teaching-learning process.Initially, it was necessary to carry out a documentary work with multiple bibliographic consultations to understand the structure and operation of the traditional methods for the conversion of rates.A tool, called the “MILHER Matrix” was built, which facilitates the work of conversion of rates for its practicality and efficiency, for which an initial experimental phase was taken and the quantitative method was used, making approchaes with key practical exercises, both teachers and students of financial mathematics.The results have been positive, since the “MILHER Matrix” contrasted with the traditional methods in terms of practicality is less complex and friendlier in its use, and in terms of efficiency it facilitates a very interesting time saving of the resource, achieving identical and similar results that with the traditional methods used for the same purpose.It is expected to continue applying this innovative educational tool with the university academic community inside and outside the country.
Keywords: Interest; Interest rate; Teaching; Learning; Banking operations